2005
DOI: 10.1111/j.1708-8240.2005.tb00472.x
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Clinical Evaluation of Nonvital Tooth Whitening and Resin Composite Restorations

Abstract: Nonvital tooth whitening is responsible for a significant change in color of endodontically stained teeth. Successful nonvital tooth-whitening therapy allows for conservative tooth preparation, preserving and reinforcing sound tooth structure. The proper use of modern adhesive systems along with resin composite restorations precludes the use of more extensive restorative treatment, delaying expensive crown and bridge procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
42
2
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 22 publications
(2 reference statements)
3
42
2
4
Order By: Relevance
“…Several laboratory and clinical studies have demonstrated carbamide peroxide or hydrogen peroxide bleaching solutions to be effective in whitening of discoloured teeth [2,4,6,16,26,27]. Thereby, efficacy might be related to the concentration of the active bleaching ingredient, the application time of the agents and the potential to penetrate dental hard tissues [10,15,22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several laboratory and clinical studies have demonstrated carbamide peroxide or hydrogen peroxide bleaching solutions to be effective in whitening of discoloured teeth [2,4,6,16,26,27]. Thereby, efficacy might be related to the concentration of the active bleaching ingredient, the application time of the agents and the potential to penetrate dental hard tissues [10,15,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…After an initial reduction of lightening possibly due to rehydration processes in the first weeks after bleaching [17,19,26] a further colour regression towards baseline shades might occur. Two-year evaluation of nonvital tooth whitening revealed a 19% reduction compared to tooth colour directly after bleaching [4]. Long-time follow-up of nightguard vital bleaching revealed colour regression in 37% of patients after 3 years and 58% after 7 years [14].…”
Section: Introductionmentioning
confidence: 99%
“…1 The decay process and/or tooth fracture may be responsible for the structural weakening of non-vital teeth; the tooth preparation required for adequate endodontic treatment may also contribute to the increased fragility. 2 After endodontic therapy, selecting the appropriate reconstruction for each non-vital tooth should be based on the remaining hard tooth structure, the number and thickness of the residual cavity walls, the position of the tooth in the arch and the load implied. Resin bonded composite (RBC) restorations showed a strengthening effect on the tooth structure, with fracture resistance similar to that of unaltered teeth.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9] With the use of improved adhesive systems in the last decade, clinicians started proposing alternative techniques to reconstruct severely damaged teeth; the main goal of the new build-up protocol is preservation and reinforcement of the remaining sound tooth structure. 2,[10][11] Although most of the coronal portion of the tooth is compromised, RBC restorations may serve to properly build-up anterior non-vital teeth by using adequate layering and curing techniques. 12 Conversely, RBC restorations are indicated in posterior teeth as long as sufficient tooth structure is preserved; more compromised teeth with missing marginal ridges and/or cusps may require placement of a post to gain additional retention of the core.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation